Nonverbal Communication Analysis in Animated Series - Zaneti, Harsa; Sari, Nopa Muspita (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
The Bilu Mela animated film is a film produced by the State of Indonesia without using sound from human dubbing, especially in dialogue. The audience is required to understand the storyline through the body movements of the Bilu Mela film characters. In the Bilu Mela episode non water ghost animation, it tells about two blue (Bilu) and red (Mela) fish sleeping in their respective aquariums. Then the blue one woke up because he heard the sound of a chest moving from outside the aquarium. Then a genie appeared who came out of the magic teapot and cursed the blue one to become long and the mela to become fat. This genie will lose his body if doused with water, so the mela watered the genie's left hand and the genie's left hand disappeared. When Bilu wanted to wash the genie's body parts, the genie apologized to Bilu not to be doused with water, Bilu agrees with the condition that the genie changes their (Bilu & Mela) bodies back to their original shape. the researcher uses the theory of non-verbal communication which can also be interpreted as the creation and exchange of messages without using words, this communication uses body movements, gestures, intonation (pitch-lowness), eye contact, facial expressions, proximity and touch - feel